Aspects of Hobbes - Malcolm, Noel (Clarendon Press ; Oxford University Press, 2002)
The author presents a set of extended essays on a wide variety of aspects of the life and work of this giant of early modern thought. An introduction to Hobbes's life and thought acts as a foundation for discussion of such topics as his political philosophy and theory of international relations.